Relation of Vitamin D levels with positive and negative symptoms of schizophrenia – A hospital based cross-sectional comparative study - Soumitra Ghosh; Bikashita Deka (Indian Journal of Psychiatry)
Background: The association between altered serum Vitamin D levels and schizophrenia has been an area that has evoked a recent fervor. The neurohumoral and neuro immunomodulatory functions of Vitamin D might have a role to play in understanding the causation of the disease and thus appear promising in the diagnostic and therapeutic frontiers of the disease. Aims and Objectives: We aimed to estimate and compare serum Vitamin D levels in drug-free cases of schizophrenia and in healthy control groups. The comparison was also made among the subgroups of positive and negative schizophrenia. Materials and Methods: The study, a hospital-based cross-sectional comparative study was carried out in the Department of Psychiatry, in a hospital in Assam over a period of 1 year. Fifty drug-free subjects of schizophrenia (Group A) diagnosed and confirmed according to International Classification of Diseases 10 were selected by consecutive sampling and 50 age and sex frequency-matched subjects (Group B) were selected from the healthy population. The cases (Group A) were divided into positive and negative groups (Group A1 and A2) based on the composite scoring of the Positive and Negative Syndrome Scale. After approval from the institutional ethics committee and obtaining written informed consent, Vitamin D levels were assessed in both groups of cases and controls and comparison was made. Results: After statistical analysis, it was seen that males were more in proportion and mostly in the age group of 20-39 years. The median Vitamin D level among the cases was 12.45 ng/mL and that among controls was 20.03 ng/mL which was statistically significant (P value .00932). Among the positive and negative schizophrenia subgroup, there was no statistically significant difference in Vitamin D levels at means of 16.54 ng/mL and 16.25 ng/Ml, respectively. The variation in Vitamin D levels in schizophrenics and the healthy population is thus discernible. Conclusion: It can be said that serum Vitamin D levels were significantly low in people with schizophrenia compared to the general population. Furthermore, it is seen that mean Vitamin D status is similar in both the groups of positive and negative schizophrenia negating the possibility of alteration of Vitamin D levels depending on the differences in symptomatology or in pathophysiology of the two groups.